1977
DOI: 10.1099/00221287-100-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Non-Helical Strain of Spiroplasma citri

Abstract: A non-helical strain of Spiroplasma citri from little-leaf diseased oranges was subcultured over 40 times in different media without producing helical cells. It was non-motile and produced colonies of a characteristic morphology on soft agar plates. Serology, DNA hybridization and toxin production confirmed that it was a strain of S. citri but its membrane protein pattern after polyacrylamide gel electrophoresis differed from those of other S. citri strains in that one band was absent. The organism caused symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 11 publications
(9 reference statements)
1
47
0
Order By: Relevance
“…Although the gradient does concentrate the fibrils, SDS-polyacrylamide gel electrophoresis (PAGE) revealed that other spiroplasmal proteins copurify with them. Spiralin, the major membrane protein of both S. citri (32) and S. melliferum (6) was reported by Townsend et al (27) to copurify with the fibrils.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the gradient does concentrate the fibrils, SDS-polyacrylamide gel electrophoresis (PAGE) revealed that other spiroplasmal proteins copurify with them. Spiralin, the major membrane protein of both S. citri (32) and S. melliferum (6) was reported by Townsend et al (27) to copurify with the fibrils.…”
Section: Methodsmentioning
confidence: 99%
“…Individual fibrils are 4 nm wide. These fibrils are made from one single protein with a molecular mass of 55 kDa (27). The protein pattern of the fibril preparation is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Saglio et al (25) and Townsend et al (32) also found a high level of relatedness among Spiroplasma citri isolates. The degree of DNA homology between the CSS and Spiroplasma citri isolates Cl89 and Cir3B is between 63 and 74% (average, 68%); in the reciprocal experiment a similar value (64 to 75% [average, 68%]) was obtained.…”
Section: Discussionmentioning
confidence: 95%